THE ROLE OF VILLAGE-OWNED ENTERPRISES (BUM Desa) IN EMPOWERING RURAL COMMUNITIES (CASE STUDY OF BUM DESA "LOH JINAWI" IN DAWU VILLAGE, PARON SUBDISTRICT, NGAWI REGENCY) - Iswari, Yolanda Ardana (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
The study focuses on the persistent lack of progress in the welfare of farmers in Ngawi Regency. This study seeks to ascertain the function of BUM Desa in fostering community empowerment, focusing on a case study conducted at BUM Desa Loh Jinawi, Dawu Village, Paron Subdistrict, Ngawi Regency, East Java Province. The research employed a descriptive qualitative methodology, utilizing an inductive approach. Data gathering procedures encompass several methods such as interviews, observation, and documentation. The collected data is subsequently subjected to the stages of data condensation, data display, and generating and validating conclusions for analysis (Miles, M. B., Huberman, A. M., & Saldana, 2014). The role of BUM Desa is reviewed through five dimensions according to Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises (BUM Desa), which then has a correlation with indicators of community empowerment (Mardikanto & Soebianto, 2019). Based on the results of the research, it is known that BUM Desa Loh Jinawi has a role as a producer of various community needs, an incubator for community businesses and in other functions that contribute to community empowerment, although the scope is still limited. The results of this study also show that the role and efforts of the BUM in Loh Jinawi Village have been able to increase the income of the farming community in Dawu Village.Keywords: BUM Desa, Community Empowerment, Increased Income